2022
DOI: 10.1002/rmv.2414
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 susceptibility and clinical outcomes in inflammatory bowel disease: An updated systematic review and meta‐analysis

Abstract: The susceptibility, risk factors, and prognosis of COVID‐19 in patients with inflammatory bowel disease (IBD) remain unknown. Thus, our study aims to assess the prevalence and clinical outcomes of COVID‐19 in IBD. We searched PubMed, EMBASE, and medRxiv from 2019 to 1 June 2022 for cohort and case‐control studies comparing the prevalence and clinical outcomes of COVID‐19 in patients with IBD and in the general population. We also compared the outcomes of patients receiving and not receiving 5‐aminosalicylates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
1
3
0
1
Order By: Relevance
“…Depending on the extent and severity of IBD, patients may receive treatment with 5-ASA, biologics, corticosteroids, thiopurines, or molecular-targeting agents. One of the most widely used drug classes is 5-ASA, which corresponds to the findings in our study [21][22][23][24]. Reports have shown that a SARS-CoV-2 infection may contribute to UC flares [25,26].…”
Section: Discussionsupporting
confidence: 90%
“…Depending on the extent and severity of IBD, patients may receive treatment with 5-ASA, biologics, corticosteroids, thiopurines, or molecular-targeting agents. One of the most widely used drug classes is 5-ASA, which corresponds to the findings in our study [21][22][23][24]. Reports have shown that a SARS-CoV-2 infection may contribute to UC flares [25,26].…”
Section: Discussionsupporting
confidence: 90%
“…Although we did not observe significant differences between COVID-19 severity groups to these comorbidities, understanding risk factors for contracting SARS-CoV-2 remains crucial for managing COVID-19 outcomes. Identifying risk factors such as hypertension, obesity, inflammatory bowel disease, and other risk factors, enables the tailoring of preventive measures and treatments, potentially mitigating the severity and spread of the disease [31,32]. Furthermore, risk factor analysis is essential for identifying vulnerable populations, allowing healthcare providers to optimize resource allocation and enhance patient care strategies during the pandemic [33].…”
Section: Discussionmentioning
confidence: 99%
“…An updated systematic review and meta-analysis by Lee et al [62] reported the susceptibility and clinical outcomes in IBD patients infected with SARS-CoV-2. IBD conditions were not associated with an increased risk of hospital or ICU admission or death, although 5-ASA and corticosteroids were associated with an increased risk for these events.…”
Section: Specific Digestive System Involvement In Covid-19 41 Pancrea...mentioning
confidence: 99%